First mission - Yao, Jiaqi (Nanyang Technological University, 2021)
‘First Mission’ is a 3D comedy short animated film about a novice Grim Reaper on his first job to reap an old man. Unlike the conventional image of a large-sized, scary, hooded reaper that has been continuously presented in films, this film seeks to bring a fresh new face of a Grim Reaper and introduce its universe to the audience. This report focuses on the process of forming the story and art direction, the technical problems encountered during the production and their solutions.